Assignment of lecturer to courses based on optimal competency scores using Modified Hungarian Method (MHM) and optimization model - Nur Syahirah Ibrahim; Adibah Shuib; Zati Aqmar Zaharudin (Penerbit Universiti Kebangsaan Malaysia, 2025)
Effective assignment of lecturers to courses is a critical task in Higher Education Institutions in ensuring optimal utilization of faculty expertise and resources. Past related studies mostly used the Hungarian assignment method while the use of Modified Hungarian Method (MHM) optimization model is still lacking. Furthermore, competency-based lecturers to courses assignment involving knowledge, skills and teaching motivation has never been implemented. This paper presents a mathematical programming approach through an enhanced formulation of the MHM model. The competency-based MHM (C-MHM) model considers the competency scores of lecturers for courses involved in which the model’s objective function is to maximize the total competency scores obtained from the lecturer-to-course assignments. Data on competency scores of lecturers across all undergraduate courses were collected from Mathematics lecturers in UiTM Shah Alam through online survey. The C-MHM model with competency scores as input data was solved using MATLAB intlinprog to generate an optimal teaching assignment plan where lecturers have been assigned to teach a maximum of three courses. The optimal solutions of this competency-based C-MHM model indicates which courses are the best to assigned to a particular lecturer based on competency levels measured using three factors namely knowledge, skills and teaching motivation. Analysis of these results reflect the proficiency and suitability of each lecturer for the assigned courses. The key contribution of the approach in our study is the adaptation of the MHM optimization model to incorporate the lecturers’ competency levels and other multidimensional inputs efficiently. The model aims to improve teaching quality, reduce mismatches, and enhance overall academic performance.